The issues of international legal personality of the individual and human rights (Journal of actual problems of jurisprudence, 2023)
In international law, a core aspect leads to the issue of the legal personality of the individual, which start to be considered specifically from mid-20th century. This was since that time the common concepts of human rights had already been worked out. The implemented international documents on human rights made it possible to come close to the solution of another equally important issue of legal personality of the individual. It should be admitted that, in the real theory of international law, this problem is not sufficiently completed, although there have already been some dramatic attempts in this direction. Even though the theme in the field of international law seems to be investigated, relating to the general concept of human rights, the problem of their relationship with the legal personality of an individual is not sufficiently discovered in international law; we set the target of defining how the study of this problem is currently under improvement integration process. Therefore, this article was aimed, first, at figured out what constitutes the basis of the legal personality of an individual. First, the article concentrated on the diverse views of scholars, and based on this, tried to find out the essence and semantic signification of each of them, as well as to determine some key elements that facilitate to define the relationship between human rights and the legal personality of an individual. Key words: individual, legal personality, human rights, concept, geopolitics.